Domestic Energy Practice in Vertical Housing - Rini Suryantini; Toga Panjaitan (Department of Architecture Universitas Muhammadiyah Jakarta, 2017)
To achieve a certain level of comfort, the main concern regarding thermal comfort in Indonesia is not about heating up the space, but rather cooling it down. In domestic environment, an active cooling activity involves energy consumption and it varies amongst households. This paper is to examine a desired level of comfort and the energy consumption in achieving the comfort level in a vertical housing for middle-low in Kemayoran, Jakarta. Whilst energy consumption in domestic environment is determined by physical factors, such as electrical appliances and spatial setting, it is also influenced by non-physical factors, such as norms and practices of the energy user. The study was conducted through field observation, mapping and structured interviews, as based for qualitative analysis. As result, various strategies in the practice are developed within the limited space by the energy user to achieve their comfort, despite the constricted supply of energy. These energy practices can be insights to a sustainable vertical housing design, in terms of achieving comfort and energy efficiency in the domestic environment.